In situ U-Pb dating and trace elements of magmatic rutile from Mujicun Cu-Mo deposit, North China Craton: Insights into porphyry mineralization - Fan Yang; Jing-wen Mao; Wei-dong Ren; Jia-run Tu; Gilby Jepson; Si-yuan Meng; Zhi-min Wang (China Geology)
ABSTRACT: Porphyry Cu (Mo-Au) deposit is one of the most important types of copper deposit and usually formed under magmatic arc-related settings, whilst the Mujicun porphyry Cu-Mo deposit in North China Craton uncommonly generated within intra-continental settings. Although previous studies have focused on the age, origin and ore genesis of the Mujicun deposit, the ore-forming age, magma source and tectonic evolution remain controversial. Here, this study targeted rutile (TiO2) in the ore-hosting diorite porphyry from the Mujicun Cu-Mo deposit to conduct in situ U-Pb dating and trace element composition studies, with major views to determine the timing and magma evolution and to provide new insights into porphyry Cu-Mo metallogeny. Rutile trace element data show flat-like REE patterns characterized by relatively enrichment LREEs and depleted HREEs, which could be identified as magmatic rutile. Rutile U-Pb dating yields lower intercept ages of 139.3–138.4 Ma, interpreted as post magmatic cooling timing below about 500°C, which are consistent or slightly postdate with the published zircon U-Pb ages of diorite porphyry (144.1–141.7 Ma) and skarn (146.2 Ma; 139.9 Ma) as well as the molybdenite Re-Os ages of molybdenum ores (144.8–140.0 Ma). Given that the overlap between the closure temperature of rutile U-Pb system and ore-forming temperature of the Mujicun deposit, this study suggests that the ore-forming ages of the Mujicun deposit can be constrained at 139.3–138.4 Ma, with temporal links to the late large-scale granitic magmatism at 138–126 Ma in the Taihang Orogen. Based on the Mg and Al contents in rutile, the magma of ore-hosting diorite porphyry was suggested to be derived from crust-mantle mixing components. In conjunction with previous studies in Taihang Orogen, this study proposes that the far-field effect and the rollback of the subducting Paleo-Pacific slab triggered lithospheric extension, asthenosphere upwelling, crust-mantle interaction and thermo-mechanical erosion, which jointly facilitated the formation of dioritic magmas during the Early Cretaceous. Subsequently, the dioritic magmas carrying crust-mantle mixing metallic materials were emplaced and precipitated at shallow positions along NNE-trending ore-controlling faults, eventually resulting in the formation of the Mujicun Cu-Mo deposit within an intracontinental extensional setting.